The Role of Islamic Boarding Schools as Character Building in Facing the Challenges of Modern Life (case study in al barokah boarding school, tunggak crème village, wonomerto district, probolinggo regency) - Muhammad Husin; Devy Habibi Muhammad; Ari Susandi (STAIFAS-Press, 2022)
The purpose of this study was to determine the extent of the role of islamic boarding school education as character building in facing modern life especially the Al Barokah boarding school. This research is structured whit a qualitative approach with data collection techniques in the form of interview, documentation, and observation. The analysis technique using reflective thinking is to combine deductive and inductive ways of thinking and then draw conclusion. Based on the analysis of the data in this study, it can be concluded that the method used by the Al Barokah Islamic Boarding School in Tunggak Cerme Village Wonomerto District Probolinggo Regency, is to improve the character of the student and their female student, by revamping the curriculum and updating management. This can be seen fro the number of qualified and comptetent alumni in all fields, both in the religious and general fields